A Convenient Preparation of Thieno[3,2-c]pyrazole - Airey, John; Barrague, Matthieu; Edwards, Michael L.; Ferro, Michael; Friedrich, Dirk; Gillespy, Timothy A.; Jurcak, John; Musick, Kwon; Weintraub, Philip M. (Synthesis, 2014)
A practical synthesis of multigram quantities of 1H-thieno[3,2-c]pyrazole is presented in which the Jacobson reaction serves as the key step.
Keywords: aminations; cyclizations; polycycles; heterocycles